Propuesta Para La Documentación Del Sistema de Gestión Ambiental con Base en la NTC ISO 14001 Del 2015 Para la Empresa Avinutrir, Ubicada en Cáqueza Cundinamarca (2022)
The present work had as purpose the design of the documentation of the environmental management system for the company Avinutrir SAS located in Caqueza Cundinamarca. The initial diagnosis of the system began, analyzing the requirements of the NTC ISO 14001: 2015 standard. Once the information was collected with a checklist, an analysis was carried out where the fulfillment of each item was defined in order to identify the number of documents necessary to comply with the provisions of the standard, followed by the analysis of compliance, an analysis of opportunities, threats, strengths and weaknesses was developed against the design of the documentation for the environmental management system in addition to a study in plant Analyzing the most significant environmental aspects of the company in order to identify opportunities for improvement, based on the analysis of information collected, the documentation required to comply with the environmental management system is designed and finally the respective cost-benefit analysis is carried out. of the implementation of the environmental management system